Dextran-based scaffolds for in-situ hydrogelation: Use for next generation of bioartificial cardiac tissues. (15th June 2021) - Banerjee, Samhita; Szepes, Monika; Dibbert, Nick; Rios-Camacho, Julio-Cesar; Kirschning, Andreas; Gruh, Ina; Dräger, Gerald
Graphical abstract: Highlights: A dextran based hydrogel is prepared for cardiac tissue engineering. The synthesis of dextran derivatives for hydrazone crosslinking is optimized. A model for the influence on phosphate ions on the gelation process is given. Successful single cell encapsulation and formation of contractile tissue is shown. The effect of RGD peptides as hydrogel modifiers is studied by RNA sequencing. Abstract: In pursuit of a chemically-defined matrix for in vitro cardiac tissue generation, we present dextran (Dex)-derived hydrogels as matrices suitable for bioartificial cardiac tissues (BCT). The dextran hydrogels were generated in situ by using hydrazone formation as the crosslinking reaction. Material properties were flexibly adjusted, by varying the degrees of derivatization and the molecular weight of dextran used. Furthermore, to modulate dextran's bioactivity, cyclic pentapeptide RGD was coupled to its backbone. BCTs were generated by using a blend of modified dextran and human collagen (hColI) in combination with induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs) and fibroblasts. These hColI + Dex blends with or without RGD supported tissue formation and functional maturation of CMs. Contraction forces (hColI + Dex-RGD: 0.27 ± 0.02 mN; hColI + Dex: 0.26 ± 0.01 mN) and frequencies were comparable to published constructs. Thus, we could demonstrate that, independent of the presence of RGD, our covalently linked dextran hydrogels are a promising matrix for building cardiac grafts.